Feed the Future Bangladesh Phase One Zone of Influence (ZOI) Endline Survey, 2018-2019 - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
The Feed the Future Phase One Zone of Influence (ZOI) Endline Survey was implemented by IFPRI through Bangladesh Integrated Household Survey (BIHS) 2018-2019. Data collection in the Feed the Future ZOI stratum took place in 20 districts in southern Bangladesh, which is divided between three divisions—that is, Barishal, Khulna, and part of the Dhaka Division—from November 2018 to February 2019. The endline survey followed the same households as the baseline, making the baseline Feed the Future ZOI Survey data directly comparable to the endline Feed the Future ZOI Survey data. Therefore, the panel format of the dataset means the economic progress of these households between 2011/2012 and 2018/2019 can be assessed. The total number of households included in Feed the Future ZOI is 2064 and is representative of Feed the Future ZOI.